Overview of Cardiomyopathies in Childhood - Rath, Anika; Weintraub, Robert (Frontiers in Pediatrics, 2021)
Paediatric cardiomyopathies are a heterogenous group of rare disorders, characterised by mechanical and electrical abnormalities of the heart muscle. The overall annual incidence of childhood cardiomyopathies is estimated at about 1 per 100,000 children and is significantly higher during the first two years of life. Dilated cardiomyopathies account for approximately half of the cases. Hypertrophic cardiomyopathies form the second largest group, followed by the less common left ventricular noncompaction and restrictive phenotypes. Infectious, metabolic, genetic and syndromic conditions account for the majority of cases. Congestive heart failure is the typical manifestation in children with dilated cardiomyopathy, whereas presenting symptoms are more variable in other phenotypes. The natural history is largely influenced by the type of cardiomyopathy and its underlying aetiology. Results from a national population-based study revealed ten-year transplant-free survival rates of 80%, 62% and 48% for hypertrophic, dilated and left ventricular noncompaction cardiomyopathies, respectively. Long-term survival rates of children with a restrictive phenotype have largely been obscured by early listing for heart transplantation. In general, the majority of adverse events, including death and heart transplantation, occur during the first two years after the initial presentation. This review provides an overview of childhood cardiomyopathies with a focus on epidemiology, natural history and outcomes.